2005
DOI: 10.1667/rr3443.1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Highly Radioresistant Malignant Hamster Fibroblasts that Survive Acute γ Irradiation with 20 Gy

Abstract: To study the acquired radioresistance of tumor cells, a model system of two cell lines, Djungarian hamster fibroblasts (DH-TK-) and their radioresistant progeny, was established. The progeny of irradiated cells were isolated by treating the parental cell monolayer with a single dose of 20 Gy (PIC-20). The genetic and morphological features, clonogenic ability, radiosensitivity, cell growth kinetics, ability to grow in methylcellulose, and tumorigenicity of these cell lines were compared. The plating efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Although H1299 is relatively radiosensitive, some cells ultimately survived and made visible colonies in the clonogenic assay (Figure 1). Many previous studies have reported that radioresistant subclones could be artificially derived from radiosensitive cancer cells (Tyrsina et al, 2005;Ogawa et al, 2006;Nojiri et al, 2009). According to our observation, it is likely that most of the genes in group A was associated with the initial step of signal transduction, which contributed as signal sensors and transducers (ATM, ATR, MRE11, 53BP1, TopBP1, Claspin and Chk2).…”
Section: Discussionmentioning
confidence: 57%
“…Although H1299 is relatively radiosensitive, some cells ultimately survived and made visible colonies in the clonogenic assay (Figure 1). Many previous studies have reported that radioresistant subclones could be artificially derived from radiosensitive cancer cells (Tyrsina et al, 2005;Ogawa et al, 2006;Nojiri et al, 2009). According to our observation, it is likely that most of the genes in group A was associated with the initial step of signal transduction, which contributed as signal sensors and transducers (ATM, ATR, MRE11, 53BP1, TopBP1, Claspin and Chk2).…”
Section: Discussionmentioning
confidence: 57%
“…Tumour cells may acquire radioresistance using multiple pathways including those which are induced/altered by ionising radiation (IR) itself ( Lee and Bernstein 1993 , Tyrsina et al 2005 , Otero et al 2006 ). To investigate IR-induced tumour radio-resistance, a radiosensitive human squamous cell carcinoma tumour, SCC61, was passed and irradiated in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In radiotherapy, suppressing the occurrence of radioresistant tumor cells and tumor repopulation are severe issues for tumor control [7], and studies to understand the cellular characteristics of repopulated tumors using model-cells have been vigorously performed recently [19][20][21][22][23]. These model-cells that survived irradiation commonly show increased malignancy with increased invasiveness, adhesion, and motility, as in clinical cases.…”
Section: Discussionmentioning
confidence: 99%